Comparative analysis of fungal communities in colonies of two leaf-cutting ant species with different substratum preferences. (June 2016) - Pereira, Jaqueline S.; Costa, Rafael R.; Nagamoto, Nilson S.; Forti, Luiz C.; Pagnocca, Fernando C.; Rodrigues, Andre
Abstract: Fungus gardens of leaf-cutting ants harbor diverse alien fungi in addition to their fungal cultivar. Previous work suggested that alien microorganisms are likely derived from the substrata foraged by ant workers and incorporated into the fungus gardens. To test this hypothesis, we sampled 1014 garden fragments from 16 field colonies of Atta sexdens rubropilosa (a dicot-cutting ant) and Atta capiguara (a grass-cutting ant) in Brazil. From a total of 615 fungal isolates recovered, we observed similar diversity of fungi between colonies of both ant species. However, fungal communities differed in composition of taxa between ant colonies. Trichoderma spirale, Trichosporon chiarellii and Penicillium citrinum were prevalent accounting for 18.5%, 12.2% and 11.7% of the total isolates, respectively. As expected, fungal communities clustered in two major groups supporting the hypothesis that plant substratum has an impact on the composition of the alien fungi found in leaf-cutting ant gardens.